The effect of microrna targeting IL17RA in regulating the expression of RANKL and OPG in stem cells from human exfoliated deciduous teeth - Keflee, Rashidi Dzul (2018)
IL17A is now becoming a key role in bone remodelling. The regulations of osteoprotegerin (OPG) and receptor activator of nuclear factor kappa-β ligand (RANKL) by IL17A were briefly explained in human mesenchymal stem cell (hMSC). Herein, the aim of the present study was to determine the potential microRNA targeting IL17RA and its effects toward OPG and RANKL expression in stem cell from human deciduous teeth (SHED). Potential microRNA was predicted by using three latest algorithmically programs such as DIANA-micro T CDS, TargetScan v7.1 and miRWalk v2.0 through a complex filtration process via in silico. The concentration of microRNA-targeting GAPDH was optimised for the most efficient downregulation of GAPDH mRNA. The concentrations of 25, 50 and 100 nM and transfection duration of 48 hours were tested with microRNA-mimic negative control (microRNA-mimic NC) as a negative control. The results showed the GAPDH mRNA level was lowest at concentration of 50 nM after evaluated by quantitative real time PCR and normalised with β-actin. This concentration can be used as the general miRNA concentration in this study. SHED was cultured in complete alpha minimum essential media (αMEM) supplemented with osteogenic media (OM) and treated with 50 ng/mL of recombinant interleukin 17A (rIL17A) for 7 days (early osteogenic phase). Treated cells were then transfected with 50 nM of positive control mimic, negative control mimic and predicted microRNAs mimic from in silico study which are hsa-miR-6761-5p and hsamiR- 4524a-3p. Downregulation of target gene and its effects towards osteogenic markers were evaluated by measuring the expressions of IL17RA, OPG, RANKL and GAPDH by quantitative real-time PCR and normalised with β-actin. Hence, transfections of both microRNA mimics showed downregulation of IL17RA gene which hsa-miR4524a-3p showed stronger downregulation (p < 0.001) when compared to hsa-miR-6761-5p (p <0.01). In addition, there was a significant downregulation of OPG expression from both microRNAs and downregulation of RANKL was also noted in both transfected SHED, however the reduction was not significant. These findings demonstrate the role of microRNA targeting IL17RA in the expression of OPG and RANKL in SHED, thus suggesting its important role in bone physiology of SHED.